THE SOCIO-POLITICAL SCENE AND HENRY’S CRISIS INFLUENCE ON THE CURRICULA OF PHYSICAL EDUCATION UNDERGRADUATE COURSES IN BRAZIL - Drigo, Alexandre Janotta [UNESP]; Silva, Luiz Henrique Da; Ferreira, Heidi Jancer [UNESP]; Silva, Cláudio Silvério Da [UNESP]; Souza, Samuel De [UNESP] (Universidade Estadual de Maringá, 2020)
From 1980s to 1990s, the Brazilian Physical Education (BPE) was strongly influenced by the discussion concerning its identity as an academic discipline; the final period of the Brazilian military dictatorship; the regulation of the BPE as a profession. Hence, this study analyzed the influence of that epistemological and political setting on the curricula of three BPE undergraduate courses. The Political Pedagogic Project and the Curriculum Matrix of the three undergraduate courses, from public universities, were analyzed using two qualitative research techniques: body of knowledge analysis, and content analysis. The results showed that the curricula analyzed did not cover a definition of professional intervention procedures based on ethical conduct specific to the area. Furthermore, the knowledge basis of the curricula is mainly constituted by discipline knowledge, which contributes to distancing the student’s training from their field of professional practice . These findings may be associated with the insufficient epistemological discussion early initiated by Henry’s works and unclear definition if the BPE is an academic or professional area. This investigation suggests that political disputes related to professionalization of BPE overlapped the academic discussions, which might have contributed to the problems identified on the preparation through bachelor courses of physical education professionals.

De 1980 a 1990, a Educação Física Brasileira (EFB) foi fortemente influenciada pela discussão sobre sua identidade como disciplina acadêmica; pelo período final da ditadura militar; e pela regulamentação da EFB como profissão. Assim, este estudo analisou a influência dessa configuração epistemológica e política sobre o currículo de três cursos de graduação em Educação Física (EF) no Brasil. O Projeto Político Pedagógico e a Matriz Curricular dos três cursos, de universidades públicas, foram analisados utilizando duas técnicas de pesquisa qualitativa: análise do corpo de conhecimento e análise de conteúdo. Os resultados mostraram que todos os currículos analisados não apresentaram uma definição clara dos procedimentos de intervenção profissional baseados em condutas éticas específicas da área. Além disso, a base de conhecimento dos currículos é principalmente constituída pelo conhecimento acadêmico, contribuindo para o distanciamento da formação do graduando com o campo de atuação profissional. Essas descobertas podem estar associadas à insuficiente discussão epistemológica que foi iniciada pelos trabalhos de Henry e a não definição se a EFB é uma área acadêmica ou profissional. Esta investigação sugere que as disputas políticas relacionadas à profissionalização da EFB se sobrepuseram às discussões acadêmicas, o que pode ter contribuído para os problemas identificados na formação do tipo bacharelado dos profissionais de EF.
O CENÁRIO SOCIOPOLÍTICO E A INFLUÊNCIA DA “CRISE DE HENRY” NOS CURRÍCULOS DE GRADUAÇÕES EM EDUCAÇÃO FÍSICA NO BRASIL
Keywords: Physical education; Curriculum; Knowledge base; Professional intervention; Educação física; Currículo; Base de Conhecimento; Intervenção profissional